2010
DOI: 10.1105/tpc.110.076927
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Framework for Flattened Leaf Blade Formation in Unifacial Leaves ofJuncus prismatocarpus     

Abstract: Angiosperm leaves generally develop as bifacial structures with distinct adaxial and abaxial identities. However, several monocot species, such as iris and leek, develop unifacial leaves, in which leaf blades have only abaxial identity. In bifacial leaves, adaxial-abaxial polarity is required for leaf blade flattening, whereas many unifacial leaves become flattened despite their leaf blades being abaxialized. Here, we investigate the mechanisms underlying the development and evolution of flattened leaf blades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
85
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 50 publications
(69 reference statements)
3
85
0
1
Order By: Relevance
“…Recent studies have revealed the molecular mechanisms underlying leaf form diversification between species (Kimura et al, 2008;Piazza et al, 2010;Yamaguchi et al, 2010;Vlad et al, 2014). However, morphological variation within a single plant is also seen in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed the molecular mechanisms underlying leaf form diversification between species (Kimura et al, 2008;Piazza et al, 2010;Yamaguchi et al, 2010;Vlad et al, 2014). However, morphological variation within a single plant is also seen in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have addressed the morphological diversification of leaves, which often vary in size, shape, and form (e.g., Blein et al, 2008;Kimura et al, 2008;Berger et al, 2009;Piazza et al, 2010;Yamaguchi et al, 2010). While often more conservative than leaves, extensive morphological diversity is also seen in stems, most dramatically with the production of tendrils, thorns, and flattened, leaf-like stems (Bell, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, developments in procedures for the analysis of molecular genetic controls of leaf organogenesis in the past decade have enabled studies on alterations in genetic systems operating in 'unusual' types of leaves (in comparison with those of Arabidopsis) (e.g., Yamaguchi et al 2010). Such evolutionary developmental biology studies or 'Evo-devo' approaches will progress rapidly in the near future with advances in Arabidopsis leaf studies.…”
Section: Introductionmentioning
confidence: 99%